Peningkatan Strategi Pemasaran untuk Perluasan Pasar dan Daya Saing UMKM Laris Bakery Snack and Cookies - Damayanti, Damayanti; Putri, Nabilla Erviana; Nisa, Dzurotun (STIE Pelita Nusantara, 2024)
Laris Bakery Snack and Cookies MSMEs is a business in the field of products and services in terms of providing or serving food requests, for various purposes such as rice boxes, bread, pastries and others. The problems faced by MSMEs are: (1) The location of Laris Bakery Snack and Cookies MSMEs is less strategic because it is in an alley, (2) Lack of product and service information regarding what customers want to order, (3) Lack of promotions to offer products and services. Some of the programs carried out by the service team include: (1) Making Stickers, Thank You Cards and Greeting Cards (2) Making Product Photos, (3) Making Brochures, (4) Making Instagram. One of the results of this community service activity program is that Laris Bakery Snack and Cookies MSMEs has a new face in terms of packaging, has attractive product photos, making brochures makes Laris Bakery Snack and Cookies MSMEs increasingly known to the public, creating Instagram for Laris Bakery Snack and Cookies MSMEs also help the online promotion process. Through improving marketing strategies, it is hoped that the market and competitive advantage for MSMEs can be expanded. Keyword: Expansion, Marketing Strategy, competitiveness and MSMEs